Temperature- and pH-Responsive Poly(NIPAM-co-HEMA-co-AAm) Nanogel as a Smart Vehicle for Doxorubicin Delivery; Combating Colorectal Cancer - Soheila Ghasemi; Mehdi Najafi; Mohammad Doroudian; Banafsheh Rastegari; Abbas Behzad-Behbahani; Hadis Soltanimehr; Fatemeh Farjadian (Gels)
In this project, a new class of temperature- and pH-sensitive hydrogel consisting of N-isopropyl acrylamide (NIPAM), hydroxyethyl methacrylate (HEMA), and acrylamide (AAm) was prepared via a controlled route through the reversible addition–fragmentation chain-transfer (RAFT) polymerization process. Poly(ethyleneglycol) dimethacrylate (PEG-DMA) was used as a long-chain hydrophilic and biocompatible crosslinking agent. The hydrogel structure was confirmed by different characteristic techniques such as 1H NMR, FT-IR, and SEC, and the morphology and particle diameters were checked via the scanning electron microscopy (SEM) and dynamic light scattering (DLS) methods. Afterward, the as-prepared hydrogel, poly(NIPAM-co-HEMA-co-AAm), was loaded with doxorubicin (DOX) to be used as a temperature- and pH-triggered delivery carrier. The prepared system released DOX slowly at 37 °C and neutral pH, but increased DOX release significantly at 42 °C and acidic pH. The anti-cancer efficiencies of free DOX, hydrogel, and the DOX–hydrogel conjugate were tested in vitro using human colorectal adenocarcinoma HT-29 cell lines. Cytotoxicity evaluation of free DOX compared with the DOX–hydrogel conjugate revealed that more cancer cells were killed with increasing concentration. Moreover, the DOX-mediated apoptosis and ROS levels showed the beneficial effects of poly(NIPAM-co-HEMA-co-AAm) hydrogel for cancer drug delivery. Generally, the results suggest that this system can be a potential candidate for designing drug delivery systems.